Prosthodontic Approaches in Compromised Hemimandibulectomy Rehabilitation: A Case Series and Treatment Algorithm - M. Shalini; Satish Kumar Gupta (Indian Journal of Dental Sciences)
Hemimandibulectomy, a surgical intervention often necessitated by neoplastic conditions or trauma, poses substantial challenges to both form and function within the oral cavity. The resultant mandibular defect disrupts the intricate balance required for mastication, speech, and facial esthetics. These case series delve into the prosthodontic management of patients who underwent hemimandibulectomy, aiming to restore both form and function. The comprehensive approach involves three different prostheses restoring posthemimandibulectomy deficits for different patients presented at different time intervals. One case involves trismus condition with upper left hemimaxillectomy and lower right hemimandibulectomy. Through a detailed exploration of these cases, the article showcases diverse challenges encountered and their modified prosthetic interventions. This compilation aims to contribute valuable insights to the prosthodontic community, offering a roadmap for addressing the unique complexities associated with hemimandibulectomy prosthesis cases.